Pengaruh Faktor-faktor Fundamental terhadap Kualitas Pengungkapan Sukarela dalam Laporan Tahunan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Budianto, Arief Satrya (Widya Mandala Surabaya Catholic University, 2009)
The purpose of this research is to find the fundamental factors that influence voluntary disclosure published in annual reports. This research used 22 manufacturing companies listed at Indonesia Stock Exchange in the period of 2006-2007, is chosen by purposive sampling. Multiple regression analysis was employed to test the research hypothesis. The result of this research how that none of the independent variables influence voluntary disclosure published in annual report.